DESAIN DAN PENERAPAN PEMBANGKIT LISTRIK TENAGA SURYA UNTUK INSTALASI PENERANGAN PADA KAPAL NELAYAN KECAMATAN PESAGUAN KANAN - Erick Radwitya (Politeknik Negeri Ketapang, 2022)
The use of solar energy is used on a fishing boat that usually uses petroleum fuel, aiming to help fishermen in technological innovation and minimize the use of petroleum as fuel on fishing boats. The process and stages in the design and construction of solar power plants on fishing boats are based on related problems regarding limited energy sources, so solar power plants are made as an alternative to lighting needs and loads on fishing boats. With a budget of Rp.2,240,000, a solar power plant can be built for lighting installations with components used by a 100 Wp solar cell, an inverter with a capacity of 500 watts, solar charge controller with a capacity of 10 A, battery with a capacity of 12 V / 50 Ah, LED, NYM cable with a size of 2 x 1.5 mm2, a single switch and MCB 2 with a capacity of 2 Amperes.